Benefits of educational plans enjoyed by UPV-Iloilo students - Castor, Thyrza; Elvas, Marianne; Mueño, Marizel; Tuvillo, Jorelle
This study, the Benefits of Educational Plans Enjoyed by the UPV-Iloilo Students aims to know the benefits received by the parents and the recipients aviling an educational plan. Questionnaires were given out to the respondents and a series of interviews were also conducted for data gathering. The data gathered were analyzed and a test was also performed to assess whether there is a relationship between the income with the premium paid, and the type of plan with the level of satisfaction derived from it. Furthermore, the effect of the parents' attitudes towards the plan, the income, and the highest educational attainment of the parents were evaluated. Aside from others factors affecting in purchasing a plan, the disadvantages and disadvantages of acquiring a plan were also identified. The researchers was able to formulate recommendations for an effective operations of the pre-need companies.